Coming Out to Siblings and Internalized Sexual Stigma: The Moderating Role of Gender in a Sample of Italian Participants. Issue 5 (20th October 2018) - Salvati, Marco; Pistella, Jessica; Ioverno, Salvatore; Laghi, Fiorenzo; Baiocco, Roberto
ABSTRACT: Previous research has shown that the act of disclosing sexual orientation, known as coming out (CO), yields various benefits for gay and lesbian (GL) persons. Moreover, some researchers have found that CO is negatively related to internalized sexual stigma (ISS). However, most research has focused on CO to parents and a few studies have examined CO to siblings. The aim of this research is to deepen the understanding of the role of CO to siblings in protecting GL persons' wellbeing. Specifically, the study used a sample of 201 Italian GL persons to determine whether CO to siblings predicted lower levels of ISS, and whether gender was a moderating factor in the relation between ISS and CO to siblings. About 62% of the sample reported that they had revealed their sexual orientation to their siblings; 71% and 62%, respectively, reported that they had disclosed their sexual orientation to their mother and father. A finding of moderate regression showed that the effect of CO to siblings on ISS was moderated by the GL persons' gender. In particular, CO to siblings was associated with lower levels of ISS in gay men but not lesbian women. Research implications and limitations are discussed.